Flock Size and Flock Composition of House Sparrow, Passer Domesticus (Linnaeus, 1758) in Tehsil Pehowa of District Kurukshetra, Haryana, India: Spatial distribution and temporal variation of house sparrow flocks in Tehsil Pehowa (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Proposed study was carried out in tehsil Pehowa of district Kurukshetra from January, 2010 to December, 2012. In tehsil Pehowa, five rural open areasrural residential premises, namely, Gauchard (PVI), Dhanipura (PV2), Bhatta majra (PV3), Nipura (PV4) and Khadaspur (PV5) five ware housesrice sellersgodowns, namely, HAFED1 (PG1), HAFED2 (PG2), Satara rice seed store godowns (PG3), Seth tara chand seed store (PG4) and Govt. ware house, Pehowa (PG5) were selected. Besides these, five number of transects (T1, T2, T3, T4 and T5) in agricultural lands and two areas of fallow lands (FL1 and FL2) were selected in tehsil Pehowa. Scan sampling method (Altman, 1974) was used in the proposed rural open areasrural residential premises, ware housesrice shellersgodowns, fallow lands, and line transect method (Sale and Berkmuller, 1988) was used in agricultural areas to record the flock size and flock composition of house sparrow. Each type of flockindividuals are age-sex wise classify and later categorized into four types i.e., all male flocks (AMF), all female flocks (AFF), mixed male-female flocks (MMF) and male-female with youngones flock (MFY) following Robinson et al., 2005. In the present study, a total numbers of 110 flocks of house sparrow, i.e., 55 flocks (in the year 2010) and 55 flocks (in the year 2011) were recorded in selected rural open areasrural residential premises. Out of these 110 flocks, 11 all male flocks (AMF), 34 all-female flocks (AFF), 62 mixed male-female flocks (MMF) and 2 male-female with youngones flocks (MFY) were observed. Total numbers of 22 flocks, i.e., 12 flocks in year 2010 while 10 blocks in year 2011 were recorded in selected ware housesrice shellersgodowns. Out of these 22 flocks, 1 all male flock (AMF), 6 all-female flocks (AFF) and 15 mixed male-female flocks (MMF). Similarly in selected agricultural areas, 8 flocks of house sparrow i.e., 5 flocks in the year 2010 and 3 flocks in the year 2011 were recorded.